Factors Influencing the Knowledge Level of Beneficiaries of Fish Farmers Development Agency (FFDA) on Scientific Fish Culture Practices in West Bengal, India (Indian Journal of Extension Education, 2018)
The present study was conducted to determine the relationship between socio-personal, socio-economic, psychological and communication variables of Fresh Water Fish Farmers Development Agency’s (FFDA) beneficiaries and their knowledge level about scientific fish culture practices. The data were collected from randomly selected 60 FFDA’s beneficiaries cum fish farmers of 4 blocks of North-24 Parganas district of West Bengal with the help of structured interview schedule. Results revealed that variables like age, farming experience, occupation, land holding, ownership of pond, fish production, annual income from fish farming, risk orientation, economic motivation and extension agency contact were significantly correlated with the knowledge level of beneficiaries. Further, to predict the extent of relationship among independent variable and knowledge level of respondents step-wise multiple regression analysis was done. From regression analysis it was found that risk orientation and occupation were found to have positive association with knowledge level at 0.05 level of probability whereas, age was found to have positive association with knowledge level of beneficiaries at 0.01 level of probability. It was also revealed that 32.3 per cent of the variations of knowledge level were due to the combined influence of these three variables.